PENGEMBANGAN VIDEO ANIMASI PEMBELAJARAN BERBASIS POWTOON PADA MATERI SISTEM RESPIRASI KELAS XI SMA - Sri Putri Ayu; Wan Syafi’i; Mariani Natalina. L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This development aims to produce a Powtoon-Based Learning Animation Video on Respiration System Material for Class XI SMA. The research was carried out at the Biology Education Study Program FKIP Riau University, SMA Negeri Plus Provinsi Riau and SMA Negeri 1 Pekanbaru from June to November 2021. The subject of this research was KD 3.4 material for the XI high school respiratory system. The type of research used is the ADDIE Research and Development model. The instruments used are validation and response questionnaires. The validation sheet consists of 4 aspects, namely the display aspect, the program aspect, the pedagogic aspect and the content aspect. The average validation result for animated video based on Powtoon based on these four aspects is 3.79 with a very valid category. The four aspects include display aspects with an average of 3.70, program aspects with an average of 3.85, pedagogic aspects with an average of 3.90 and content aspects with an average of 3.72. The results of the limited trial phase 1 obtained an average score of 3.76 in the very good category. While the results of the limited trial phase 2 obtained an average score of 3.80 in the very good category. The results showed that the animation video based on Powtoon on the respiratory system material for class XI Senior High School is of high quality and suitable to be used as a learning medium.Key Words: Learning Animation Video, Powtoon, Respiratory System.